Employment Law, Contracts, and Their Implementation Dynamics in the Construction Sector: A Global Perspective - Utomo, Bagus Satrio; Priyono, Joko; Trihastut, Nanik (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study analyzes the implementation of employment contracts in the construction sector across selected countries and assesses how national laws and regulations influence this implementation. The study scope is limited by the number of countries examined and the qualitative methodology employed, suggesting opportunities for broader, mixed-methods research in the future. A key contribution is the focused examination of the right to safe working conditions within employment contracts. Using a combined legal and empirical approach, the research integrates a systematic literature review of relevant legislation and contractual practices with thematic analysis of qualitative data from in-depth interviews with industry stakeholders. Findings reveal significant cross-country differences in the enforcement and content of employment contracts, particularly regarding workers’ rights, wage payment systems, and job satisfaction. National legal frameworks play a decisive role in shaping these variations. Persistent challenges include precarious and informal employment, as well as the misclassification of workers as independent contractors. The research bridges general employment regulations with sector-specific realities, highlighting the need for tailored legal and policy responses. The findings offer guidance for policymakers seeking to strengthen labor protections, for construction firms aiming to improve contractual fairness and worker satisfaction, and for workers advocating for their rights. The study emphasizes the importance of consistent, equitable legal frameworks in ensuring dignified working conditions across diverse national contexts.